The role of the private sector in the promotion of young entrepreneurship in Nigeria - Nwoye, May Ifeoma
Several strategies have been employed in Nigeria in an effort to develop economic growth. This study shows that the private sector, as opposed to the public sector, is the major growth area for developing entrepreneurship.
Within the past few decades, Nigeria's search for economic relief has often compelled her to employ several strategies of varying dimension to achieve the desired objectives through development of the public sector. But the impact of these strategies has not been far reaching in developing entrepreneurship because of the numerous political and economic determinants that have bedevilled the country's public sector. This paper argues that if the public enterprise were operated and managed more effectively and efficiently, its contribution to the country's economic development would have been far greater than it is currently. Disappointingly, the public sector tends to be rather slow, bureaucratic and without clear objectives; there are also issues of corruption and mismanagement. The private sector, on the other hand, is considered to be more dynamic, innovative and result oriented. This has led to the conclusion in this paper that the private sector is the major engine of growth in promoting young entrepreneurship, given the enabling environment.
Keywords: Entrepreneurship--Nigeria.